State-building in Afghanistan : The role of institutional capacity - Kohistani, Sardar M.; Justus Liebig University Giessen (My University, 2009)
Today, Afghanistan represents one of the most poor, instable and insecure countries of the world. It is important to notice that the negative impact of its problems (e.g. terrorism, drug trafficking and migration) do not remain exclusively within its borders but also have worldwide effects. Recent studies categorize Afghanistan among the countries in the world that are regarded as failed states, failing states, collapsed states, weak states, fragile states, crisis states.This study analyzes the processes of state-building in Afghanistan from the initial stages the country emerged as a political entity to the current situation. For such an analysis the available publications written in Farsi, Pashtu, English and German were used. In order to analyze recent development in Afghanistan field researches were carried out in which up-to-date statistical data was collected. Furthermore, the result of a questionnaire distributed to over 247 people and interview with experts are used in this study.Major focus is concentrated on the role of institutional capacity in the state-building process. As this study argues institutional capacity has always constituted one of the major challenges for state-building. Due to this problem, despite Afghanistan became independent, it never became a stable and functioning state. Today it characterizes a fragile state and institutional capacity is the major factor behind its fragility. Meanwhile, institutional capacity represents the ability and will of the actors (human resource) who play their part in the creation or reform of institutions and economic mobilizations. In the case of Afghanistan, its diverse ethno-linguistic and socio-religious structure plays a determining role in the creation and reform of institutions. The main actors dominated the society are the tribal, religious and intellectual elites. These three actors have seldom been in peace with each other. In order to maintain their political interests each established different ruling system in the country. They rarely shared power or worked together. Almost each ruled for sometime but was challenged or overthrown by its rival opposition. In order to succeed in this rivalry they repeatedly searched help form outside. At the same time, Afghanistan inherited its diversity from its geographical position between Central Asia, South Asia and the Middle East which made it vulnerable to many invasions through the course of history. These three regions share close cultural relationships with Afghanistan. Any political development and conflict in these regions externally affected the process of state-building and at different period of time e.g., the British and the Russian during the Great Game, the East and West during the Cold War, and finally the New Great Game and the War on Terror. Therefore internal rivalry backed by external rival powers undermined the sustainability and legitimacy of the political system in the country.According to the findings of the current study weak institutional capacity remains the major problem of state-building process as a result of which Afghanistan as a state can not fulfill its basic functions. The weakness of institutional capacity is the result of legitimacy crisis, incompatibility of the political system and institutions in the country. These four problems are closely linked with one another. This study suggests that building a stable state in Afghanistan crucially requires human and financial resources. The provision of these two elements is highly dependent to a sense of unity among the diverse population. Such a sense of unity can only be created and strengthened when the political structure matches the demand and requirement of the population. The state should no longer represent an oppressive and aggressive body. State institutions should no longer be abused against the population. Instead they should perform their functions for the welfare and prosperity of the population. This will help to minimize the traditional gap between the population and state authorities

Heute gehört Afghanistan zu den ärmsten, instabilen und unsichersten Ländern der Welt. Der negative Impakt der Probleme (z.B. Terrorismus, Drogenhandel und Migration) beschränkt sich nicht allein auf die Staatsgrenzen, sondern hat weltweite Auswirkungen. Jüngste Studien kategorisieren Afghanistan als gescheiterter , scheiternder , kollabierter , schwacher , fragiler oder Krisen - Staat.Diese Arbeit analysiert den Prozess der Staatsbildung in Afghanistan von der Gründung bis zur aktuellen Situation. Dafür wurden Quellen in Farsi, Paschtu, Englisch und Deutsch ausgewertet. Während der Feldforschungsaufenthalte wurden aktuelle statistische Daten erhoben, ein Fragebogen wurde ausgeteilt und von 247 Personen beantwortet, sowie mehrere Experteninterviews geführt.Der Fokus dieser Arbeit liegt auf der Rolle der institutionellen Kapazität, die eine entscheidende Rolle im Staatsbildungsprozess spielt. Die fragile Lage Afghanistans ist auf die schwache institutionelle Kapazität der Institutionen zurückzuführen. Institutionelle Kapazität bezeichnet die Kompetenz und den Willen der Akteure, die beim Aufbau und der Reform der Institutionen mitwirken. Im Fall von Afghanistan sind die vielfältigen ethno-linguistischen and sozio-religiösen Strukturen determinierende Faktoren der institutionellen Kapazität. Die Hauptakteure der Gesellschaft Afghanistans entstammen den tribalen, religiösen und intellektuellen Eliten, die eigennützige Regierungssysteme implementierten und eine Teilung der Macht nicht vorsahen.Die aktuelle Untersuchung zeigt, dass eine schwache institutionelle Kapazität das Hauptproblem der Staatsbildung Afghanistans ist, weil die Institutionen ihre Grundfunktionen beim Staagtsaufbau nicht wahrnehmen können. Eine große Herausforderung ist die Überbrückung der Distanz zwischen der Bevölkerung und den staatlichen Autoritäten.
Staatsbildung in Afghanistan : Die Rolle der institutionellen Kapazität
Keywords: Afghanistan; Fragiler Staat; Institutionelle Kapazität; Höhere Bildung; Politische Geographie; Afghanistan; Fragile State; Institutional Capacity; Political Geography; Higher Education; ddc:550